2013
DOI: 10.1017/s0030605311001803
|View full text |Cite
|
Sign up to set email alerts
|

Large carnivore attacks on humans in central India: a case study from the Tadoba-Andhari Tiger Reserve

Abstract: We examined human and ecological attributes of attacks by tigers Panthera tigris and leopards Panthera pardus on humans in and around the Tadoba-Andhari Tiger Reserve in the Chandrapur District of central India to provide recommendations to prevent or mitigate conflicts between people and large carnivores. During 2005–2011 132 carnivore attacks on humans occurred, 71 (54%) of which were lethal to humans. Tigers and leopards were responsible for 78% and 22% of attacks, respectively. Significantly more victims w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 25 publications
3
50
1
Order By: Relevance
“…However, this result does not corroborate the previous studies. Pant et al [9] reported that death cases caused by elephant were higher (88%) in the central Nepal, but the death cases caused by tigers were lesser (54%) in the Tadoba-Tiger Reserve in India [27]. Mayer [44] stated about three-fold more fatalities (15%) caused by wild boar attacks than the recorded fatalities caused by wild boars (4%) in CNP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this result does not corroborate the previous studies. Pant et al [9] reported that death cases caused by elephant were higher (88%) in the central Nepal, but the death cases caused by tigers were lesser (54%) in the Tadoba-Tiger Reserve in India [27]. Mayer [44] stated about three-fold more fatalities (15%) caused by wild boar attacks than the recorded fatalities caused by wild boars (4%) in CNP.…”
Section: Discussionmentioning
confidence: 99%
“…According to Parker et al [26], people's behavior to a large extent depends highly on incentives; formulating an incentive mechanism in a society that would promote the intended behavior among people is very important. The studies suggested that vulnerabilities to the lives and livelihoods of the people to attack are influenced not only by the biology of animals, but also by socio-economic factors, gender, activities, the age of victims [4,[8][9][10][11]14,19,27], the attitude and perceptions of the people, the place, season and time, the population, and the movement of conflicting wildlife species.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…This leads to an intensification of conflict between the growing tiger population and a human population of 1.25 billion increasing at a rate of 1.7% annually (Chandramouli, 2011). Dispersing tigers from protected reserves are prone to confrontations with humans, resulting in human-tiger conflict (Dhanwatey et al, 2013). Isolation and inadequate reserve size (average size is 486 km 2 , Karanth and Defries, 2011) amongst sites that harbors the fragmented tiger populations highlight the need of connecting these forest patches and the importance of corridors in doing so.…”
Section: Introductionmentioning
confidence: 99%
“…Human-wildlife conflict has a history of high prevalence at TATR. A study published in 2013, focusing on attacks on humans by tigers and leopards in and around TATR, surveyed 132 reported incidents of conflict in the six years from 2005-2011 (Dhanwatey et al, 2013), reporting a notable increase over the course of the two decades. More than half of these incidents (54%) resulted in fatalities for humans involved.…”
Section: Human-wildlife Conflict At Tatrmentioning
confidence: 99%
“…Collecting fuelwood is often a solitary activity, particularly for women, hence leaving the collectors more vulnerable to attacks. Furthermore, the collection itself requires crouching or bending over, which makes for easier targets for tigers and leopards (Dhanwatey et al, 2013).…”
Section: Human-wildlife Conflict At Tatrmentioning
confidence: 99%